INFLUENCE OF MOTOR CAPaBILITIES AND COGNITiVE CHARACTERISTICS ON SPEED OF LEADING THE BALL AND ACCURACY IN BASKETBALL - Rašid Hadžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
In goal of for ti fi ca tion the sca le of in fl u en ce of mo tor ca pa bi li ti es and cog ni ti ve cha rac te ri stics on re sult suc cess in ball le a ding speed and si tu a te ac cu racy in ba sket ball re sults de ri ved from sam ple of 105 boys bet we en 14 and 16 years ha ve been analyzed. Re gres si ve analyze of cri te ria va ri a ble SMKVLS and va ri a ble SMKBVL gi ves suf fi ci ent in for ma tion abo ut in fl u en ce of ap plied mo tor and cog ni ti ve on suc cess of per for ming of tre a ted cri te ria va ri a ble